MEDIA PEMBELAJARAN MENGENAL SATWA LANGKA MENGGUNAKAN AUGMENTED RALITY - Aiwan Kisra Febryan; Suharyanto, Cosmas (LPPM Universitas Putera Batam, 2022)
This study aims to analyze the application of learning methods to recognize endangered animals using augmented reality which is applied in Baiturrahmah Kindergarten in Batam city. This application results in changes in the teaching and learning process at Baiturrahmah Kindergarten. TK Baiturrahmah is located in Kav. Sagulung Baru block A RT.01 RW.03, Sungai Binti, Kec. Sagulung, Batam City, Prov. Riau islands. This research is a qualitative research with analytical methods using data collectors. Based on the results of the study, with the existence of software that makes it easier for the teacher to carry out teaching and learning. However, there are several things that need to be considered, namely on several objects, besides that, although the application of the learning method is sufficient for teaching and learning needs in Baiturrahmah Kindergarten, both the principal and the teachers still do not quite understand the learning method. In the end, this learning media still cannot be fully utilized optimally.